Energy and fuel consumption forecast by retrofitting absorption cooling in Malaysia from 2012 to 2025 - Shekarchian, M.; Moghavvemi, Mahmoud; Motasemi, F.; Zarifi, F.; Mahlia, T.M.I. (Elsevier, 2012)
Electricity demand in residential and commercial sectors has increased steadily over the past 50 years in Malaysia. The bulk of which is being consumed by air conditioning systems. Absorption cooling systems can be a reasonable alternative to have conditioned spaces in the country. The fuel consumption to produce electricity for cooling purposes in residential and commercial sectors has been forecasted from 2012 to 2025. The paper also investigates the effect of applying five different scenarios on energy and fuel consumption by retrofitting absorption chillers instead of conventional cooling systems. This study found that the consumption of natural gas will be raised by increase in utilized absorption chillers however, the consumption of different fuels such as coal, diesel and fuel oil will decrease in thermal power plants.